Uji Efektivitas Antidiabetes Kombinasi Ekstrak Buah Pare (Momordica charantia L.) Dan Kelopak Bunga Rosella (Hibiscus sabdariffa L.) Pada Tikus Jantan Putih Sebagai Hewan Percobaan - Anggun Syafitri (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2022)
Diabetes mellitus is a chronic metabolic disease characterized by an increase in blood glucose levels which can be treated with traditional treatments derived from plants. One of the example is a plant that can reduce blood glucose levels are bitter melon and rosella which contain flavonoids to reduce blood glucose by increasing cell sensitivity to insulin and stimulating insulin release in pancreatic β cells. The objective of the research is to determine the effect of the combination of bitter melon extract and rosella petal extract in reducing blood glucose levels compared to glibenclamide. The method of the research is an experimental study used 21 rats induced by alloxan and divided into 7 groups. Extraction using maceration method with 80% ethanol. From the results of the study, each treatment group experienced a decrease in blood glucose levels. From the 7 treatment groups, the best reduction in blood glucose levels were the third combination group. Among the three combination groups, the combination dose of 225 mg/kgBB of bitter melon and 195 mg/kgBB of rosella flower petals was the best compared to glibenclamide in reducing blood glucose levels. The conclusion of the research is combination of bitter melon extract and rosella flower petals have an effect that are more effective in reducing blood glucose levels compared to glibenclamide and their single extract.